2016
DOI: 10.1016/j.bbagen.2016.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Intrahippocampal administration of a domain antibody that binds aggregated amyloid-β reverses cognitive deficits produced by diet-induced obesity

Abstract: Background The prevalence of high fat diets (HFD), diet-induced obesity (DIO) and Type 2 diabetes continues to increase, associated with cognitive impairment in both humans and rodent models. Mechanisms transducing these impairments remain largely unknown: one possibility is that a common mechanism may be involved in the cognitive impairment seen in obese and/or diabetic states and in dementia, specifically Alzheimer’s disease (AD). DIO is well established as a risk factor for development of AD. Oligomeric amy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 98 publications
0
12
0
Order By: Relevance
“…The body operates poorly under obese conditions. In particular, when compounded by age, hippocampal functions can become impaired [ 27 , 28 ]. We looked at age-related markers of peripheral and hippocampal health, with or without the addition of long-term obesity, and determined that SAMe supplementation is beneficial to aged mice across all measurements, but the positive effects of SAMe were diminished with obesity.…”
Section: Discussionmentioning
confidence: 99%
“…The body operates poorly under obese conditions. In particular, when compounded by age, hippocampal functions can become impaired [ 27 , 28 ]. We looked at age-related markers of peripheral and hippocampal health, with or without the addition of long-term obesity, and determined that SAMe supplementation is beneficial to aged mice across all measurements, but the positive effects of SAMe were diminished with obesity.…”
Section: Discussionmentioning
confidence: 99%
“…In this point, an important question arises: what is the molecular link between diet, T2DM and cognitive impairment? In this regard, Osborne et al (2016) reported that intrahippocampal infusion of an Aβ33–42 gamma antibody reversed cognitive impairment in rats with HFD-related cognitive loss. Hence, these results stressed the role of soluble Aβ in obesity-mediated cognitive loss and they are in agreement with previous studies hypothesizing that diffusible Aβ oligomers are responsible for neural dysfunction leading to AD (Walsh et al, 2005; Tarasoff-Conway et al, 2015; Xia et al, 2016; Bu et al, 2018; Hurtado-Puerto et al, 2018).…”
Section: Obesogenic Diet As a Risk Factor For Cognitive Impairmentmentioning
confidence: 99%
“…It has been shown AD is highly observed in states, in which the consumption of diets high in and calorie is high (Martin et al, 2014). Diet-induced obesity (DIO) is linked to cognitive defect and pathological alterations similar to changes observed in AD (Heyward et al, 2012;Yang et al, 2013;Boitard et al, 2014;Osborne et al, 2016). Although eating a highfat diet (HFD) affects AD-associated pathology in different animal models and conditions (Grant, 1999;Grillo et al, 2011;Soares et al, 2013;Hsu and Kanoski, 2014), the mechanisms linking risk factors to AD pathogenesis are not still clear (Thériault et al, 2016).…”
Section: Introductionmentioning
confidence: 99%